Two new enchytraeid species from Jeju Island, Korea (Annelida, Clitellata) - Klára Dózsa-Farkas; Tamás Felföldi; Hajnalka Nagy; Yong Hong (ZooKeys, 2019)
The enchytraeid fauna of three areas in Jeju Island (Korea) was studied, and comparative morphological and molecular taxonomic examinations (based on CO1, ITS and H3 sequences) were performed on nine samples collected in 2016. Twenty-two enchytraeid species were recorded and identified. The descriptions of two new species (Achaeta multisacculata sp. n. and Fridericia floriformis sp. n.) are presented in this paper. The main diagnostic features of A. multisacculata sp. n. are: three pairs of pyriform glands per segment, clitellum with two “baguette-like” packages of glands, dorsal blood vessel from VII, secondary pharyngeal glands absent, oesophageal appendages well developed, two pairs of preclitellar nephridia, the reproductive organs (except the spermathecae in V) shifted one segment forward. The main features of F. floriformis sp. n. are that they are large worms, have up to 2–4 chaetae in bundles, strong body wall, thick cuticle, five pairs of preclitellar nephridia, c-type coelomo-mucocytes sometimes with some refractile vesicles, chylus cells in XII–XV, sperm funnels approximately twice as long than wide, spermathecae with long ectal duct without glands, ampullae surrounded distally by about 9–12 sessile diverticula of varying size. Molecular phylogenetic analyses supported the morphological results and confirmed the status of the two new species.